Economic Analysis of Islanded Microgrid: A Case Study of Kisiju Village - Coastal Region - Mnyanghwalo, Eva; Masenge, Irene H.; Justo, Jackson J.; Mwasilu, Francis (Tanzania Journal of Engineering and Technology, 2022)
The concept of Microgrid (MG) has gained significant attention of researchers and projects on the business side of electrical power generation and utilization, particularly in electrification of islanded areas such as villages. Most of these microgrids are powered by renewable energy resources (RERs) and they distribute power in low voltage distribution networks. Hence, these systems are faced with reliability problems due to the intermittency nature of RERs which affect the technical as well as the return on Investment of specific projects. In the latter context, reliability and economic analysis of the MG systems is an inevitable choice. This paper presents an economic and reliability analysis of the solar PV (SPV) MG system installed at Kisiju village, located in the Coastal area of Mkuranga district in Tanzania, where operational costs, running costs and return value on investment of the installed MG system is discussed and analysis of the reliability of the system to consumers is performed and the results are validated using HOMER software. Key words: Renewable Energy Resources (RERs), Distributed Generation (DG), islanded, Microgrid (MG), reliability and economic analysis, Solar Photovoltaic (SPV).